Effect of Thunbergia laurifolia water extracts on hepatic insulin resistance in high-fat diet-induced obese mice - Jarinyaporn Naowaboot; Urarat Nanna; Linda Chularojmontri; Pholawat Tingpej; Patchareewan Pannangpetch (Asian Pacific Journal of Tropical Biomedicine, 2021)
Objective: To examine the effect of water extract of Thunbergia laurifolia on hepatic insulin resistance in high-fat diet-induced obese mice. Methods: High-fat diet with 45 kcal% lard fat was used for obesity induction in ICR mice. The mice were fed with high-fat diet for 16 weeks, and during the last 8 weeks, they were treated with 200 mg/ kg/day of water extracts from Thunbergia laurifolia leaf, stem and flower. Serum biochemistry, liver histology, and protein expression were examined after the treatment. Results: Extracts from all of the three parts of Thunbergia laurifolia significantly alleviated hyperglycemia, hyperlipidemia, hyperinsulinemia, and hyperleptinemia. The stem and flower extracts improved glucose tolerance. All of the extracts significantly reduced serum TNFα and monocyte chemoattractant protein-1 levels. Liver weight, triglyceride levels, and lipid accumulation were also decreased. Moreover, hepatic glucose-6-phosphatase level was significantly decreased, while the levels of PPARα, phosphorylated AMPK, and phosphorylated Akt were significantly increased with treatment of Thunbergia laurifolia extracts. Conclusions: Thunbergia laurifolia extracts can ameliorate hepatic insulin resistance in high-fat diet-induced obese mice by improving glucose and lipid homeostasis, which may be associated with stimulating phosphorylation of AMPK and Akt pathways.